The assertiveness workbook : how to express your ideas and stand up for yourself at work and in relationships - Paterson, Randy J. (Oakland, CA : New Harbinger Publications, 2022)
'Assertiveness is a critical skill that influences both professional success and personal happiness. With more than 100,000 copies sold, this self-help classic by psychologist Randy J. Paterson-author of How to Be Miserable-is now fully revised and updated. With this workbook, readers will learn to set and maintain boundaries, assert themselves constructively, and be more genuine in their relationships'--
Print version record.
Includes bibliographical references.
Added to collection customer.56279.3
Keywords: Assertiveness (Psychology); Assertiveness (Psychology)